PEMANFAATAN MEDIA PEMBELAJARAN AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 5 DI SD NEGERI 090 PALEMBANG TAHUN PELAJARAN 2023/2024 - Silaturrahmi, Mutiara; Adib, Abdul; Setyaningsih, Rina (UNISAN JURNAL, 2024)
Along with the development of modern technology as it is today, its role can support teaching and learning activities, where the role of technology is already so prominent, especially in countries that have been developing for a long time. In this case, the government and society pay special attention to the world of education, because they realize the importance of education carried out supported by the role and function of the technology.In a learning process that can be said to be effective if a teacher has the ability to manage teaching material so that students easily accept the material being taught and can stimulate students to express their ideas, while differences in students become more creative and respect each other's opinions. Based on the above, the authors take the formulation of the problem in this study, namely "How to Utilize Audio Visual Learning Media in Improving Learning Outcomes of Islamic Religious Education at Elementary School SD Negeri 090 Palembang".The purpose of this study is to describe the use of Audio Visual Media in improving student learning outcomes and student learning outcomes after using audio visual media in class V Islamic religious education subjects at di SD Negeri 090 Palembang State Elementary School. This research is a descriptive qualitative research, where several methods were used to collect data, namely observation, interviews and documentation. the steps taken are data reduction, data display (presentation of data), verification (drawing conclusions). from the data collected, the writer analyzes that by way of inductive thinking that departs from specific conclusions then becomes a conclusion. The results of the study found that the use of Audio Visual learning media in improving learning outcomes of Islamic Religious Education for class V was said to be effective because PAI teachers could use Audio Visual Media properly and well and could produce good learning outcomes. Audio Visual Media For teachers can facilitate the transformation of knowledge while for students can be useful as motivation to learn.